Retroperitoneal isolated enteric duplication cyst - Fariha Akil Fazal; Patricia Okiro (Elsevier, 2020)
Enteric duplication cysts are rare congenital malformations of the gastrointestinal tract with an estimated incidence of 1:100,000 live births. Fewer still are isolated enteric duplication cysts (IEDC). Accurate diagnosis and timely excision of IEDCs can help in avoiding possible complications including bleeding from gastric mucosa and malignant transformation later in life. Currently, in the paediatric population, there are twenty reported cases in the literature worldwide. Of these, only three have been described in the retro peritoneum. We present a retroperitoneal IEDC, which was juxtaposed to the inferior vena cava. To the best of our knowledge, this has not been reported before in literature. Keywords: Isolated enteric duplication cyst, Inferior vena cava, Abdominal pain